The impact of financial liberalization on private banking investment in the Iraqi economy for the period (2004 - 2015) - صاحب نعمة العكايشي; فاطمة سلام عبد (Iraqi Journal for Administrative Sciences, 2024)
This research tried to explain the effect of financial liberalization on private investments through selected banking system indicators. And the (Jarque – Bera) test proved the normal distribution of all research variables, the (ADF) test shows, especially in the absence of a constant and trend and At the level, the stability of time series of research variables when significance levels (1% and 5%). And based on the analysis, statistical and econometrics tests, it show the positive and significance impact of variables of the private banks capital, private banks assets, private sector deposits and private banking credit in private banking investment, Where the rise of (1%) leads to a rise of (42%, 66%, 73% and 33%), respectively, indicating that the most prominent impact is the index of private sector deposits.